Socialization and Assistance in Making Soap From Used Cooking Oil As an Effort to Utilize Household Waste - Kasman, Risqah Amaliah; Indris, Siti Indriyati; Addas, Reski Kartini; Haeriani, (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2025)
The use of cooking oil at the household level is a basic necessity since many foods are processed through frying. Used cooking oil is often disposed of improperly, leading to environmental damage as it is considered waste. This community service activity aims to provide outreach and assistance to households in utilizing waste cooking oil to add value rather than discarding it carelessly or consuming it in an unfit condition. This activity was conducted in Taroada Village, Turikale District, Maros Regency. The goal of this activity is to educate household members by providing guidance on soap making from waste cooking oil. The method used in this study is service learning, in which the material is delivered through hands-on soap-making practice and a question-and-answer session to encourage active participation. The result of this activity is that the community becomes aware of the health and environmental impacts of waste cooking oil and learns how to recycle it into soap.